Assessing the Contributions of Comet Impact and Volcanism Toward the Climate Perturbations of the Paleocene‐Eocene Thermal Maximum. Issue 24 (27th December 2019) - Liu, Zeyang; Horton, Daniel E.; Tabor, Clay; Sageman, Bradley B.; Percival, Lawrence M.E.; Gill, Benjamin C.; Selby, David
Abstract: The Paleocene‐Eocene Thermal Maximum is marked by a prominent negative carbon‐isotope excursion, reflecting the injection of thousands of gigatons of isotopically light carbon into the atmosphere. The sources of the isotopically light carbon remain poorly constrained. Utilizing a multiproxy geochemical analysis (osmium isotopes, mercury, sulfur, and platinum group elements) of two Paleocene‐Eocene boundary records, we present evidence that a comet impact and major volcanic activity likely contributed to the environmental perturbations during the Paleocene‐Eocene interval. Additionally, Earth system model simulations indicate that stratospheric sulfate aerosols, commensurate with the impact magnitude, were likely to have caused transient cooling and reduced precipitation. Plain Language Summary: The Paleocene‐Eocene Thermal Maximum ( 55.9 Ma) records a period of climate warming associated with the injection of thousands of gigatons of carbon into the atmosphere. However, the sources of the carbon are still unclear. Our study uses geochemical data (osmium isotopes, mercury, sulfur, and platinum group elements) of two North Atlantic Ocean drill cores across the Paleocene‐Eocene interval to suggest that both a comet impact and large‐scale volcanism occurred at that time. The comet is estimated to be small ( 3.3 km diameter) with 0.4 Gt carbon and thus cannot be responsible for the Paleocene‐Eocene Thermal Maximum. However, climate modeling suggests that the comet impact might have caused transient cooling and reduced precipitation. Key Points: A multiproxy geochemical study supports claims that both a comet impact and volcanism occurred at the Paleocene‐Eocene boundary The comet is estimated to be small with 0.4 Gt carbon Climate modeling indicates that the comet impact might have caused transient cooling and reduction in precipitation